Moisture content measurements in wood using dual-energy CT scanning – a feasibility study. Issue 5 (19th October 2016) - Lindgren, Owe; Seifert, Thomas; Du Plessis, Anton
ABSTRACT: Currently computed tomography (CT) scanning provides a non-destructive method to determine moisture content in wood in three dimensions. With the current methodology two measurements are needed, one with the scanned piece of wood's moist state and one after drying. Then the difference of the images can be calculated. The drawback and challenge is that dimensional changes due to shrinkage of wood in the drying process have to be compensated for by image processing. In this study a dual-energy CT scanning method is tested based on the consecutive scanning of wood samples at different energy levels to differentiate water from wood, without the necessity to dry the sample and thus without the need for complex image correction. Not quantified but visible differentiations due to moisture content were obtained on small cubical pine samples of different densities by quick consecutives scans at 60 and 200 kV. The results suggest that given that the pixels in the CT images are representing absorption coefficients it should be possible to directly measure moisture content in wood non-destructively in small volume elements inside solid wood in three dimensions. Further applications of this technique in industrial CT scanning of wood are discussed.